Sustainable Development Goals (SDGs) and Indonesian Housing Policy - Saddam Rassanjani (Department of Government Studies Universitas Muhammadiyah Makassar, 2018)
The main objective of the implementation of Sustainable Development Goals (SDGs) in Indonesia is to bring accelerated development in all aspects so that the poverty rate is expected to decrease even disappear. One of the programs that aimed to reduce poverty rates in Indonesia is the provision of housing for the community, especially the underprivileged. Moreover, it is a the million houses program that proclaimed by the Ministry of Public Works and People's Housing, and this program is correlated with the SDGS, especially goal 11 (sustainable cities and communities). The research is relying on secondary data basis primarily from books, journals, published reports and online news. It is expected that this study is able to provide a new insight for the government in building a community residential area, which is to integrate development plans into three dimensions (social, economic, and environment) which are the pillars of sustainable development. Unfortunately, nowadays the government is relying too hard on achieving quantity and a little focus on quality. Furthermore, an experience on the MDGs edition can be an important lesson for the government in realizing SDGs, especially now that SDGs are in line with the points that contained in the RPJMN. Therefore, if the government is able to maximise this global development agenda, it is not impossible that the million houses program can be one of the leading programs in overcoming the problem of poverty, especially housing shortage in Indonesia.